Comparative study on health-related quality of life of farmers and workers - Liu, Xiaofang; Dong, Hengjin (Value in health regional issues, 2017)
To estimate and compare the health-related quality of life (HRQOL) between Chinese farmers and workers and study the relationships between the sociode…
Gesehen am 22.11.2018